The cinnamon bun book store ebook - Gilmore, Laurie (Dream Harbor, 2024)
From the author of the viral TikTok phenomenon, The Pumpkin Spice Cafe, comes a new seasonal spicy romance! 'Unputdownable, I devoured [it] within days... Dream Harbor is not short of a vibrant and hilarious cast of characters to help breathe life into the already charming town' ⭐⭐⭐⭐⭐ Every book in the Dream Harbor series can be read as a standalone. 'A charming break from reality' Publishers Weekly When a secret message turns up hidden in a book in the Cinnamon Bun Bookstore, Hazel can't understand it. As more secret codes appear between the pages, she decides to follow the trail of clues... she just needs someone to help her out. Gorgeous and outgoing fisherman, Noah, is always up for an adventure. And a scavenger hunt sounds like a lot of fun. Even better that the cute bookseller he's been crushing on for months is the one who wants his help! Hazel didn't go looking for romance, but as the treasure hunt leads her and Noah around Dream Harbor, their undeniable chemistry might be just as hot as the fresh-out-of-the-oven cinnamon buns the bookstore sells... The Cinnamon Bun Book Store is a Sunday Times and USA Today bestselling cozy romantic mystery with a HEA guaranteed! Tropes: opposites attract small town forced proximity he falls first Readers have fallen for Laurie Gilmore 'I absolutely loved this small town, cosy romantic and very steamy novel just as much as The Pumpkin Spice Cafe' ⭐⭐⭐⭐⭐ 'Wonderful story with tears, laughter, mysteries, uncertainty and happiness' ⭐⭐⭐⭐⭐ 'Compelling, cozy and delightful narrative' ⭐⭐⭐⭐⭐ 'A charming small town romance with sizzling chemistry and plenty of spice' ⭐⭐⭐⭐⭐ 'I LOVED THIS SO BAD. The vibes of the small town were immaculate' ⭐⭐⭐⭐⭐ 'This book makes my heart happy!' ⭐⭐⭐⭐⭐ 'The perfect kind of romance for me' ⭐⭐⭐⭐⭐ 'Perfect for reading in the evening with a little fire going' ⭐⭐⭐⭐⭐ 'I enjoyed this so much! Completely heartwarming and unputdownable, the steamy scenes were a bonus' ⭐⭐⭐⭐⭐ '[This] gave me everything I needed from an easy read and was the perfect addition to the Dream Harbor series' ⭐⭐⭐⭐⭐ 'I read it in one sitting because I couldn't bear to put it down' ⭐⭐⭐⭐⭐ 'Just the perfect amount of sugar and spice... a literal dream to read' ⭐⭐⭐⭐⭐